When the Data Are Out: Measuring Behavioral Changes Following a Data Breach - Turjeman, Dana; Feinberg, Fred M. (Marketing Science, 2024)
This paper investigates users’ reactions to a massive and highly sensitive data breach via an array of causal inference methodologies.